(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2016)
Digital technologies are now embedded in our society. Focus has shifted from whether or not to use them in teaching and learning, to understanding which technologies can be used for what specific educational purposes and then to investigate how best they can be used and embedded across the range of educational contexts in schools. The new digital technologies have permeated economy markets, politics, our workplaces, the ways we communicate with each other, our home activities, as well as operation of all levels of education from kindergarten to doctoral studies. The new technologies challenge higher education institutions worldwide to redefine their student constituencies, their partners and competitors and to redesign their research infrastructures and teaching practices. The focus of this paper is to examine the role of Information and Communication Technology|(ICT) in higher education in India. the emergence of ICT has fundamentally changed the practices of not only business and governance but education as well. While the world is moving rapidly towards digital media.The role of ICT in education has become increasingly important. There has been an unprecedented growth in the use of ICTs in teaching, research and extension activities. The sudden boom in information Technology has transformed the way how knowledge is disseminated today. One of the changes it has brought about is the way how teachers interact and communicate with the students and vice-versa.